2014
DOI: 10.1074/jbc.m113.541458
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Diverts Dividing Osteoblastic Precursor Cells to an Adipogenic Pathway and Induces Synthesis of a Hyaluronan Matrix That Is Adhesive for Monocytes

Abstract: Background: Adipocytes accumulate in diabetic bone marrow. Results: Bone marrow stromal cells that divide in hyperglycemia divert from the osteoblast lineage to pathological adipogenesis and produce an extensive monocyte-adhesive hyaluronan matrix with consequent demineralization of trabecular bone. Conclusion: This mechanism diminishes the stromal cell population with an accumulation of metabolically stressed adipocytes. Significance: This provides new insights into diabetic osteopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 66 publications
3
36
0
Order By: Relevance
“…Monocytes recognize and adhere to these modified HA structures (14, 21). These leukocyte-adhesive HA matrices are present in many pathological conditions, including lung biopsies from asthmatic patients (21), responses of smooth muscle cells to ER stress at physiological normal levels of glucose (31,32), wound healing (33), idiopathic pulmonary hypertension (18), airway smooth muscle cells in vitro (32), airway interstitial cells in mouse asthma models (19), renal tubular endothelial stress (34,35), and adipocytes in a diabetic rat model (36,37). However, in this study we show that murine AECs behave differently than the other cell types reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes recognize and adhere to these modified HA structures (14, 21). These leukocyte-adhesive HA matrices are present in many pathological conditions, including lung biopsies from asthmatic patients (21), responses of smooth muscle cells to ER stress at physiological normal levels of glucose (31,32), wound healing (33), idiopathic pulmonary hypertension (18), airway smooth muscle cells in vitro (32), airway interstitial cells in mouse asthma models (19), renal tubular endothelial stress (34,35), and adipocytes in a diabetic rat model (36,37). However, in this study we show that murine AECs behave differently than the other cell types reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several soluble growth factors and cytokines[21-25] in the extracellular matrix (ECM)[26, 27] have a role in directing the fate of these cells. Native hyaluronan (HA) and osteopontin, which are ligands for CD44, support the proliferation and differentiation of these adipose derived stem cells into adipocytes[28-32]. While native, high molecular weight HA supports survival, proliferation and differentiation of pre-adipocytes, fragmentation of HA suppresses adipocyte maturation.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In the insulin-deficient form of the disease, this leads to diminished bone density, with human studies and streptozotocin-induced diabetic animal models noting a decrease in trabecular bone mass and a reciprocal increase in the adiposity of the marrow. [16][17][18][19][20] Alternatively, analyses of bones of type 2 diabetics have generally observed unchanged or increased bone mineral density, though clinically, both diabetic populations have a substantially increased risk of fractures in comparison to non-diabetics. 18,[21][22][23][24] Additionally, there is increasing evidence that some diabetic medications may negatively impact bone density and marrow adiposity.…”
Section: Diabetes and Its Complicationsmentioning
confidence: 99%